ENSURING OF FINANCIAL STABILITY OF THE ENTERPRISE BY FINANCIAL MANAGEMENT TOOLS - Saidov Khabibulla Shavkat ogli (Journal of new century innovations, 2023)
Abstract. The article contains the author's methodological toolkit for managing the financial stability of an industrial enterprise, as well as the results of its use. To manage the financial stability of an industrial enterprise, it is proposed to form signal indicators that allow evaluating the work of circulating capital management. For this, it is proposed to make evaluation according to the following groups of signal indicators: indicators characterizing the level of receivables; indicators characterizing the level of external obligations of the enterprise. The result of the author's algorithm use is the determination of the integral indicator of financial stability, the value of which includes three components: structure indicators, dynamics indicators and indicators of the intensity of the obligations use.